2019
DOI: 10.1007/s13770-019-00198-8
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Functional Cell Sheets with Human Thyrocytes from Non-Tumorous Thyroid Tissue

Abstract: BACKGROUND: Engineered cell sheet transplantation has been considered an alternative physiological therapy for endocrine disorders. In this study, we attempted to fabricate functional human thyroid cell sheets using the engineering technology by culturing primary thyrocytes in free-feeder monolayers and assessed their proliferation and function in two different media. METHODS: The non-tumorous tissues (approximately 2 g) were dissected during surgery. Primary human thyroid cells were isolated by mechanical dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…68 This technology enables preparation of transplantable tissue constructs preserving intact cell-cell contacts and extracellular matrices. 67 In the authors' laboratory, these cell sheets were successfully generated: hepatic cell, 69 thyrocyte, 70 myoblast, 71 adiposederived stem cell, 72 oral epithelial cell, 73 islet cell, 74 fibroblast, 75 and epidermal cell 76 sheets.…”
Section: Cell Sheetsmentioning
confidence: 99%
“…68 This technology enables preparation of transplantable tissue constructs preserving intact cell-cell contacts and extracellular matrices. 67 In the authors' laboratory, these cell sheets were successfully generated: hepatic cell, 69 thyrocyte, 70 myoblast, 71 adiposederived stem cell, 72 oral epithelial cell, 73 islet cell, 74 fibroblast, 75 and epidermal cell 76 sheets.…”
Section: Cell Sheetsmentioning
confidence: 99%
“…Techniques based on cell sheets [3] and cell aggregates [4] can improve engraftment after transplantation. Several studies have demonstrated hormone secretion by bioengineered endocrine tissue, including islet β-cell sheets [5], islet β-cell spheroids [6] and islet-like organoids [4,7] in models of diabetes mellitus, and thyroid cell sheets [8,9] and thyroid gland organoids [10] in models of hypothyroidism.…”
Section: Introductionmentioning
confidence: 99%
“…Several researches have used a strategy based on culturing cells on tissue culture plates (TCPs) with unique polymer coating. [4][5][6][7][8] For example, poly(N-isopropylacrylamide) (PNIPAAm) has been applied to the surface of TCP for detaching cells since PNIPAAm can change its hydrophilicity in temperature-dependent manner. 5 However, PNIPAAm has several disadvantages.…”
Section: Introductionmentioning
confidence: 99%